An increase in immature β-cells lacking Glut2 precedes the expansion of β-cell mass in the pregnant mouse - Beamish, Christine A. (PLoS One, 2017)
A compensatory increase in β-cell mass occurs during pregnancy to counter the associated insulin resistance, and a failure in adaptation is thought to contribute to gestational diabetes. Insulin-expressing but glucose-transporter-2-low (Ins(+)Glut2(LO)) progenitor cells are present in mouse and human pancreas, being predominantly located in extra-islet β-cell clusters, and contribute to the regeneration of the endocrine pancreas following induced ablation. We therefore sought to investigate the contribution of Ins(+)Glut2(LO) cells to β-cell mass expansion during pregnancy. Female C57Bl/6 mice were time mated and pancreata were collected at gestational days (GD) 6, 9, 12, 15, and 18, and postpartum D7 (n = 4/time-point) and compared to control (non-pregnant) animals. Beta cell mass, location, proliferation (Ki67(+)), and proportion of Ins(+)Glut2(LO) cells were measured using immunohistochemistry and bright field or confocal microscopy. Beta cell mass tripled by GD18 and β-cell proliferation peaked at GD12 in islets (≥6 β-cells) and small β-cell clusters (1–5 β-cells). The proportion and fraction of Ins(+)Glut2(LO) cells undergoing proliferation increased significantly at GD9 in both islets and clusters, preceding the increase in β-cell mass and proliferation, and their proliferation within clusters persisted until GD15. The overall number of clusters increased significantly at GD9. Quantitative PCR showed a significant increase in Pdx1 presence at GD9 vs. GD18 or control pancreas, and Pdx1 was visualized by immunohistochemistry within both Ins(+)Glut2(LO) and Ins(+)Glut2(HI) cells within clusters. These results indicate that Ins(+)Glut2(LO) cells are likely to contribute to β-cell mass expansion during pregnancy.